A clinical and pathological update on hepatocellular carcinoma - Salvatore Lorenzo Renne; Luca Di Tommaso (Korean Liver Cancer Association, 2022)
It is estimated that more than 1 million individuals will be affected annually by hepatocellular carcinoma (HCC) by 2025. HCC can be broadly grouped into two major molecular subgroups, each of which is characterized by specific morphological and phenotypic features that mirror the genetic background. The use of these tissue biomarkers in the daily practice of pathologists promises to better allocate patients with HCC with adequate treatments. In turn, this will likely boost the attitude of clinicians toward obtaining a pre-treatment biopsy.